2008
DOI: 10.1111/j.1744-1617.2008.00215.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation Among Types of Intimate Partner Violence: Research Update and Implications for Interventions

Abstract: A growing body of empirical research has demonstrated that intimate partner violence is not a unitary phenomenon and that types of domestic violence can be differentiated with respect to partner dynamics, context, and consequences. Four patterns of violence are described: Coercive Controlling Violence, Violent Resistance, Situational Couple Violence, and Separation-Instigated Violence. The controversial matter of gender symmetry and asymmetry in intimate partner violence is discussed in terms of sampling diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
594
4
22

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 609 publications
(644 citation statements)
references
References 82 publications
24
594
4
22
Order By: Relevance
“…They tend to have quite conservative attitudes toward women, although this may make them appear similar to jealous Dysphoric-Borderline men. Consistent with the work of Johnson (2006) and Kelly and Johnson (2008), Holtzworth-Munroe and Meehan (2004) show that the violence of "Family Only" batterers tends to be less intentionally controlling and more contextually driven than that of domestic violence perpetrators with antisocial or borderline personality disorders; a finding UK researchers have also replicated (Dixon and Browne 2003). Meanwhile, Stuart et al (2006) provide some support for Kelly and Johnson's claims about the way in which Violent Resistance emerges as a response to Coercive Control.…”
Section: Personality Typessupporting
confidence: 87%
See 2 more Smart Citations
“…They tend to have quite conservative attitudes toward women, although this may make them appear similar to jealous Dysphoric-Borderline men. Consistent with the work of Johnson (2006) and Kelly and Johnson (2008), Holtzworth-Munroe and Meehan (2004) show that the violence of "Family Only" batterers tends to be less intentionally controlling and more contextually driven than that of domestic violence perpetrators with antisocial or borderline personality disorders; a finding UK researchers have also replicated (Dixon and Browne 2003). Meanwhile, Stuart et al (2006) provide some support for Kelly and Johnson's claims about the way in which Violent Resistance emerges as a response to Coercive Control.…”
Section: Personality Typessupporting
confidence: 87%
“…The other two groups of men identified by Holtzworth-Munroe and Stuart were more likely to be coercively controlling in the ways described by Johnson (2006), Kelly andJohnson (2008), andStark (2007). According to Holtzworth-Munroe and Stuart, the Dysphoric-Borderline group engaged in violence that could be severe and occasionally extra-familial.…”
Section: Personality Typesmentioning
confidence: 93%
See 1 more Smart Citation
“…Clearly most violence is perpetrated by men (Black et al, 2011) and the severity of levels and rates of IPV is higher for men (Archer 2000;Stith et al, 2008;Tjaden & Theonnes, 2000). However, research has shown that both men and women perpetrated IPV (Archer, 2000;Kelly & Johnson, 2008;Stith & Straus 1995). Given the complexities of IPV, research indicating that both genders perpetrate IPV, and the research on subtypes of IPV (Johnson, 2005(Johnson, , 2006Johnson & Ferraro, 2000), I suggest that males and females do not differ on their levels of IPV.…”
Section: Gender and Ipvmentioning
confidence: 99%
“…This model refers to the conflict between the two partners where physical aggressive acts are tactics used in response to a conflict, as opposed to the coercive approach in unilateral violent relationships. Situational couple violence occasionally takes place when conflict gets out of hand: it is not a general means of controlling the other partner but it is the result of a temporary attempt to establish control during a conflict (Johnson, 1995;Kelly & Johnson, 2008). This pattern of aggression is characterized by gender symmetry, defined as equivalent rates of partner violence by males and females (Archer, 2000;Frieze, 2005) and is distinct from the coercive approach, where one partner, usually the male, is the perpetrator and the other the victim and where physical aggression is a means of maintaining a general control over the partner.…”
Section: Reciprocal Dating Aggressionmentioning
confidence: 99%